2009 IEEE International Conference on Wireless and Mobile Computing, Networking and Communications 2009
DOI: 10.1109/wimob.2009.39
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting RF-Scatter: Human Localization with Bistatic Passive UHF RFID-Systems

Abstract: In ubiquitous computing, localization of users in indoor environments is a challenging issue. On the one hand, localization data needs to have fine granularity to provide reasonable input for intention recognition and task planning. On the other hand, effects like multi-path interference and signal scattering of RF propagation in indoor environments reduces the accuracy of traditional wireless localization techniques. However, we prove that such adversary effects can be characterized and utilized conversely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…1. The results provide a maximum RMSE of 0.75 m [1].  Geometric localization based on Linear Least Squares and Intersection Points applied on the measured signal strength differences.…”
Section: A Passive Rfid Positioningmentioning
confidence: 96%
See 2 more Smart Citations
“…1. The results provide a maximum RMSE of 0.75 m [1].  Geometric localization based on Linear Least Squares and Intersection Points applied on the measured signal strength differences.…”
Section: A Passive Rfid Positioningmentioning
confidence: 96%
“…Dealing with the problem of energy efficiency and deployment complexity we invented an approach utilizing ground mounted passive Radio Frequency Identification Tags (RFID) for device-free radio-based recognition [1], [3], [4]. This work has shown that it is possible to calculate 2D user positions with remarkable accuracy [4] and low computational complexity.…”
Section: A Passive Rfid Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of RFID-based IPSs by adopting passive RFID tags have been proposed in recent two decades [17,18]. Although they are lighter and less expensive than active tags, the range of the passive RFID tags is limited to approximately 1 to 2 m which largely restricts the coverage area of their system [19].…”
Section: Rfid-based Ipsmentioning
confidence: 99%
“…In addition, Yang et al [7] introduced a method using a compressed infrared bearing sensor for human localization as infrared detectors are sensitive to the change of infrared radiation induced by human motions. In [8], an approach for human localization using a passive UHF RFID was presented. The idea is to characterize the change of RSSI caused by the presence of a person inside an RFID augmented deployment area.…”
Section: Introductionmentioning
confidence: 99%